Mesenchymal Stem Cells Alleviate Post-resuscitation Cardiac and Cerebral Injuries by Inhibiting Cell Pyroptosis and Ferroptosis in a Swine Model of Cardiac Arrest - Xu, Jiefeng; Zhang, Minhai; Liu, Fei; Shi, Lin; Jiang, Xiangkang; Chen, Chuang; Wang, Jiangang; Diao, Mengyuan; Khan, Zafar Ullah; Zhang, Mao (Frontiers in Pharmacology, 2021)
Following cardiopulmonary resuscitation (CPR), the ensuing cardiac and cerebral injuries contribute to the poor outcome of cardiac arrest (CA) victims, in which the pathogenetic process is possibly driven by cell pyroptosis and ferroptosis. Mesenchymal stem cells (MSCs) have been shown to be a promising strategy for post-resuscitation cardiac and cerebral protection in rat, but its effectiveness in the clinically relevant swine model and the potential protective mechanism remain unknown. The present study was designed to investigate whether MSCs administration could alleviate post-resuscitation cardiac and cerebral injuries through the inhibition of cell pyroptosis and ferroptosis in swine. Twenty-four male domestic swine were randomly divided into three groups: sham, CPR, and MSC. A dose of 2.5×106/kg of MSCs derived from human embryonic stem cells was intravenously infused at 1.5, and 3 d prior to CA. The animal model was established by 8 min of CA and then 8 min of CPR. After resuscitation, cardiac, cerebral function and injury biomarkers were regularly evaluated for a total of 24 h. At 24 h post-resuscitation, pyroptosis-related proteins (NLRP3, ASC, cleaved caspase-1, GSDMD), proinflammatory cytokines (IL-1β, IL-18), ferroptosis-related proteins (ACSL4, GPX4) and iron deposition in the heart, cortex and hippocampus were measured. Consequently, significantly greater cardiac, cerebral dysfunction and injuries after resuscitation were observed in the CPR and MSC groups compared with the sham group. However, the severity of cardiac and cerebral damage were significantly milder in the MSC group than in the CPR group. In addition, the expression levels of NLRP3, ASC, cleaved caspase-1, GSDMD and ACSL4, the contents of IL-1β and IL-18, and the level of iron deposition were significantly higher while the expression level of GPX4 was significantly lower in the heart, cortex and hippocampus in all resuscitated animals compared with the sham group. Nevertheless, MSCs administration significantly decreased post-resuscitation cardiac, cerebral pyroptosis and ferroptosis compared to the CPR group. Our results showed that the administration of MSCs significantly alleviated post-resuscitation cardiac and cerebral injuries in swine, in which the protective effects were related to the inhibition of cell pyroptosis and ferroptosis.